The political process in Kazakhstan at the present stage - A. S. Seidumanov (Проблемы постсоветского пространства, 2018)
In recent decades, the political process in Kazakhstan has gone through several stages of its development. Each of them was associated with the specifics development of the Kazakh state, reflecting, among other things, the level of economic and social development.After gaining independence, the political process in Kazakhstan was held in the conditions of growing economic problems, reorientation of trade and economic relations. The country’s leadership faced the need to address urgent socio-economic tasks and, at the same time, to prevent political chaos and anarchy.Formation and subsequent development of the institution of the presidency, the formation of the party system, the development of parliamentarism required the alterations, and subsequently the adoption of a new version of the Basic Law of Kazakhstan. Its adoption made it possible to achieve the functioning of a strong presidential power in the country, combined with the presence of ideological pluralism, the development of the party system.The problems of Kazakhstan’s political development were constantly in the field of view of the country’s leadership. After 2007, the president of the country initiated a course for a gradual redistribution of powers between the executive and legislative branches of power. The task was set to expand the powers of the legislature, while maintaining a strong presidential branch of power. Such changes were dictated by the tasks of Kazakhstan’s political development, its economy, active participation in integration projects, as well as greater involvement of the country in world political processes.In the past few years, the political process in Kazakhstan has been marked by large-scale changes that reflect the incompleteness of political reform. A key element of the transformation is the creation of a system of power in which strengthening the presidential-parliamentary form of government will reflect the need to strengthen the role of parties. At the same time, in 2017– early 2018 various initiatives aimed at enhancing the stability of the existing political system are discussed in the country, which should give greater stability and predictability to the political process in Kazakhstan, creating the basis for its stable social and economic development.